Analysis of the DPR's Position in the Process of Forming Islamic Law in Indonesia Based on Taqnin Theory - Arsadani, Qosim; Andriyani, Elisa Eka (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2024)
This article explores the role of Indonesia's People's Representative Council (DPR) in shaping Islamic law, employing the Taqnin theory as a guiding framework. Taqnin theory is a crucial conceptual tool in understanding how the DPR contributes to crafting legislation aligning with Islamic principles. Beyond its legislative function, the DPR serves as an interpreter of religious precepts, navigating the intersection between Islamic values and societal needs. By applying Taqnin Theory, the DPR crafts laws in line with Islamic teachings and ensures their relevance within evolving social contexts. The analysis underscores the DPR's role in formulating laws reflecting Islamic values while considering formal legal, moral, and ethical dimensions inherent in Islamic teachings. This process illustrates the active engagement of the DPR in crafting laws that not only address religious imperatives but also respond to social exigencies and communal values. Despite the constructive guidance provided by Taqnin Theory, the article also addresses challenges in its implementation, such as interpretational disparities, community resistance, and political dynamics shaping Islamic law formation in Indonesia. As outlined in the article, the historical trajectory of Islamic law legislation in Indonesia offers insight into its evolution from the colonial era to its integration into the national legal framework. By examining the status of Islamic law in Indonesia, the article delineates the dynamics of a legal system comprising national and customary laws. While Islamic law significantly influences domains such as marriage, inheritance, and Sharia-compliant financial institutions, the foundational principles of Pancasila embody a state ethos characterised by inclusivity and tolerance towards religious and cultural diversity. Moreover, the article underscores the positive legal outcomes of applying Taqnin, underscoring its significance in understanding the process of Islamic law formation in Indonesia.